Efficacy of geraniol but not of β-ionone or their combination for the chemoprevention of rat colon carcinogenesis - Vieira, A.; Heidor, R.; Cardozo, M. T.; Scolastici, C.; Purgatto, E.; Shiga, T. M.; Barbisan, L. F. [UNESP]; Ong, T. P.; Moreno, F. S. (Associação Brasileira de Divulgação Científica (ABRADIC), 2011)
β-ionone (βI), a cyclic isoprenoid, and geraniol (GO), an acyclic monoterpene, represent a promising class of dietary chemopreventive agents against cancer, whose combination could result in synergistic anticarcinogenic effects. The chemopreventive activities of βI and GO were evaluated individually or in combination during colon carcinogenesis induced by dimethylhydrazine in 48 3-week-old male Wistar rats (12 per group) weighing 40-50 g. Animals were treated for 9 consecutive weeks with βI (16 mg/100 g body weight), GO (25 mg/100 g body weight), βI combined with GO or corn oil (control). Number of total aberrant crypt foci (ACF) and of ACF ≥4 crypts in the distal colon was significantly lower in the GO group (66 ± 13 and 9 ± 2, respectively) compared to control (102 ± 9 and 17 ± 3) and without differences in the βI (91 ± 11 and 14 ± 3) and βI+GO groups (96 ± 5 and 19 ± 2). Apoptosis level, identified by classical apoptosis morphological criteria, in the distal colon was significantly higher in the GO group (1.64 ± 0.06 apoptotic cells/mm²) compared to control (0.91 ± 0.07 apoptotic cells/mm²). The GO group presented a 0.7-fold reduction in Bcl-2 protein expression (Western blot) compared to control. Colonic mucosa concentrations of βI and GO (gas chromatography/mass spectrometry) were higher in the βI and GO groups, respectively, compared to the control and βI+GO groups. Therefore, GO, but not βI, represents a potential chemopreventive agent in colon carcinogenesis. Surprisingly, the combination of isoprenoids does not represent an efficient chemopreventive strategy.
Keywords: Colon; Carcinogenesis; Chemoprevention; β-ionone; Geraniol; Isoprenoid; Acyclic monoterpene